Integrasi RBV, RDT, DCT, dan SCT dalam Menjelaskan Disiplin dan Kinerja Karyawan PT Bridgestone - Rusman, Rusman; Hendayana, Yayan (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to integrate five major theoretical frameworks—Firm Performance Theory, Resource-Based View (RBV), Resource Dependency Theory (RDT), Dynamic Capabilities Theory (DCT), and Social Cognitive Theory (SCT)—to explain employee performance at PT Bridgestone Tire Indonesia, Bekasi Plant, Cutting Department. By combining these frameworks, the study provides a comprehensive understanding of how organizational resources, environmental dependencies, adaptive capabilities, and social-cognitive mechanisms interact to shape work outcomes. Empirical data is drawn from Rusman (2025), who analyzed both the mediating role of work discipline and the moderating role of work motivation in influencing performance. The findings indicate that internal resources such as human capital, knowledge, and technical skills, as well as external resource dependencies, significantly impact work discipline and overall firm performance. Dynamic capabilities allow employees and the organization to adapt to changing conditions and optimize resource utilization effectively. In parallel, social cognitive factors—including self-efficacy, observational learning, and social reinforcement—play a critical role in shaping employee behavior and discipline. Moreover, work motivation strengthens the relationship between discipline and performance, suggesting that highly motivated employees are more likely to translate disciplined behavior into measurable performance outcomes. These results highlight that organizational excellence is not solely determined by material resources or structural factors but depends on a synergistic combination of systemic resource management, adaptive capabilities, and individual psychological engagement. The study underscores the importance of aligning motivational strategies, discipline management, and resource optimization to achieve sustainable high performance in competitive industrial settings.